Segregation, science and commissions of enquiry: The contestation of native education policy in South Africa 1930-36 - Krige, Sue (My University, 1996)
This paper focuses on debates around African education which emerged from two State initiated commissions and an education conference in the period 193 0-193 6: the 1932 Natives Economic Commission (NEC), the 1935-6 Interdepartmental Committee into Native Education (Welsh Committee) and the New Education Fellowship (NEF) Conference of 1934. The paper highlights the responses of the English-speaking Protestant missions to two major and intermeshing trends which affected African education during this period, secularisation and segregation. In the history of South African education, a clear but neglected theme which emerges in the period after the First World War is the desire of the mission churches to resist State control, and to retain control of their schools in terms of administration, appointment of staff and curriculum content. Implicit in the struggle over control of African education were important issues such as the location and nature of expertise, what constitutes worthwhile knowledge, the most appropriate schooling system for imparting knowledge and the political consequences of such policy. Through the lens of debates around African education, global and colonial trends such as the rise of science, the secularisation of knowledge and the concomitant emergence of the "expert" can be seen. This paper argues that church responses to these trends incorporated more than merely an outdated reliance on nineteenth century Cape liberalism and notions of assimilation. They drew on an emerging critique of segregation and the illiberal use of science and expertise which emerged both from South Africa and from the British colonial experience elsewhere in Africa.
African Studies Seminar series. Paper presented 29 April 1996. Not to be quoted without the Author's permission.
Keywords: Blacks. Education. South Africa; Indigenous peoples. Education. South Africa; Education and state. South Africa; Education. South Africa. History